The importance of community for species survival. A sociobiological perspective - Elżbieta Czykwin (Studia z Teorii Wychowania)
The problem of the survival of human societies in the face of global crises raises the question: how did the communities of other living creatures deal with crises over hundreds of thousands of years? Analysis of crisis coping mechanisms by elephant communities; of whales and sparmaceta whales and siberian foxes - they are examples of common and important characteristics that developed in the process of evolution as a response to environmental conditions. The direction of changes in these characteristics is par excelance social and is directed at the common good. Thus, it has a pro-social character and glorifies altruism.Also in relation to human development from the sociobiological perspective - one can point to the same characteristics revealing their importance and role in the adaptation process. The example of the survival of homo sapiens and the extinction of homo neanderthalensis (Neanderthal man) are a spectacular example of this.Such characteristics as friendliness, altruism, solidarity, responsibility, concern for the common good, prosociality have become the guarantors of survival in opposition to aggression and selfishness. In the area of culture, it is expressed in the tendency to transfer the content and standards important for the survival of WE to the area of IAM awareness. The above-mentioned characteristics, which have an anti-authoritarian and pro-democratic dimension, thus become standards for the development of human civilizations. The persistence of the timeless values that the Decalogue brings, and thus sacrifice for others and "loving your neighbor as yourself", are an example of the importance of understanding community.The characteristics important for adaptation are somehow intuitively sensed and visible in the cultural tendencies of pro-social democratic societies, expressed in community tendencies. In this context, the importance of friendship is directly related to the length and quality of human health and life.